Mehr Gerechtigkeit durch den Gesundheitsfonds? - Gerlinger, Thomas; Mosebach, Kai; Schmucker, Rolf (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
In Germany since more than a decade one reform of the health care system follows the next one. The newest reform, which shall bring more competition between public health insurances, is analysed. It is shown that this reform will increase the burdens of persons with lower income and gives shelter to the insurance privileges of persons with higher income.